Electrophysiological effects of E-3753, a new antiarrhythmic drug, in guinea-pig ventricular muscle. - Delpón, E. (1989)
1. The electrophysiological effects of E-3753, a new antiarrhythmic drug, were studied in guinea-pig papillary muscles. 2. E-3753 (10(-7) - 10(-4) M) produced a concentration-dependent decrease in the action potential amplitude and Vmax of the upstroke, shortened the action potential duration (APD) and shifted the resting membrane potential to less negative values. E-3753 also shortened the effective refractory period (ERP), lengthening the ERP relative to APD. 3. E-3753 (10(-5) M) shifted the membrane responsiveness curve along the voltage axis to more negative potentials. 4. In the presence of E-3753 (10(-5) M) trains of stimuli at rates between 0.5 and 3 Hz led to an exponential decline in Vmax (onset rate at 3 Hz, 0.05 +/- 0.009 per action potential), to a new steady-state level. This use-dependent Vmax block was augmented at higher rates of stimulation. The time constant for the recovery of Vmax from the use-dependent block was 41.1 +/- 4.8 s. 5. E-3753 (10(-5) - 10(-4) M) had no effect on the characteristics of the slow action potentials elicited by isoprenaline in ventricular fibres depolarized by 27 mM KCl. 6. The slow onset of use-dependent block during repetitive activity and the slow offset kinetics of use-dependent Vmax block suggest that E-3753 exhibits class Ic antiarrhythmic actions in ventricular muscle fibres but does not exhibit class IV (Ca antagonist) antiarrhythmic actions.